Dying to ask 38 questions from kids about death - Duthie, Ellen 1974-; Juan Cantavella, Anna 1978- (Tra Publishing, 2024)
For mortal beings of all ages comes Dying to Ask, a book born out of an international project where children were invited to ask questions about death based on a series of workshops. The result? Hundreds of questions from countries all over the world. Herein lies thirty-eight questions that best represented the breadth and depth of children’s interest in death and related matters, complete with psychological and scientific proofing. Thoughtful, tender, and surprisingly joyful, this illustrated book is an invitation to talk, think, and ask further questions about death.
Originally published in Spanish 2023 as ¿Así es la muerte? : 38 preguntas mortales de niñas y niños by Wonder Ponder, Madrid
Keywords: Kinderfrage; Tod; Death / Juvenile literature; Children and death / Juvenile literature; Enfants et mort / Ouvrages pour la jeunesse; Kindersachbuch